2015
DOI: 10.1016/j.scog.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive normality in schizophrenia revisited

Abstract: The validity and significance of normal range neurocognition in schizophrenia remain unclear and controversial. We assessed whether normal range patients and controls demonstrate evidence of decline relative to premorbid ability and differ in performance profiles across measures, including those external to the normality criterion. In addition, we compared below normal range healthy control participants with patients at the same ability level. Performance normality was defined as a MATRICS Consensus Cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
5
17
1
Order By: Relevance
“…In the present study, the dn-FES group showed severe and widespread cognitive deficits in all domains, and this observation was consistent with the previous studies that used the same instrument [5,35,36]. Schizophrenia has distinct cognitive impairments, including speed of processing [37], working memory [38], verbal learning [39], reasoning/problem solving [40], visual learning [41], attention/vigilance [42], and social cognition [43]. Our results showed that cognitive deficits were present at the onset of schizophrenia without considering the several factors, such as long-term antipsychotic treatment and prolonged illness course.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the dn-FES group showed severe and widespread cognitive deficits in all domains, and this observation was consistent with the previous studies that used the same instrument [5,35,36]. Schizophrenia has distinct cognitive impairments, including speed of processing [37], working memory [38], verbal learning [39], reasoning/problem solving [40], visual learning [41], attention/vigilance [42], and social cognition [43]. Our results showed that cognitive deficits were present at the onset of schizophrenia without considering the several factors, such as long-term antipsychotic treatment and prolonged illness course.…”
Section: Discussionsupporting
confidence: 92%
“…We found that SZ patients showed cognitive impairments in all domains, which is consistent with previous studies that used the same cognitive measurement [15]. Deficits processing speed [33], working memory [34], verbal learning [7], reasoning/problem-solving [35], visual learning [36], and attention/vigilance [37] were found in SZ patients. Similar cognitive impairments were also reported in studies investigating patients with other psychiatric diagnoses [3841]; however, the cognitive deficits were not as severe or as widespread as those seen in SZ patients.…”
Section: Discussionsupporting
confidence: 88%
“…The anterior region in the frontal lobe forms the supplementary motor area. Processing speed is important for SZ patients, and impairment in this area has been widely reported in previous studies [13, 15, 33]. Impairment in processing speed is an important factor for predicting the functional outcome of SZ patients [4548].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the dn-FES group showed severe and widespread cognitive deficits in all domains, and this observation was consistent with previous studies that used the same instrument [33][34][35]. Schizophrenia has distinct cognitive impairments, including speed of processing [36], working memory [37], verbal learning [38], reasoning/problem solving [39], visual learning [40], attention/vigilance [41], and social cognition [42]. Our results showed that cognitive deficits were present at the onset of schizophrenia without considering the several factors, such as long-term antipsychotic treatment, prolonged illness course.…”
Section: Discussionsupporting
confidence: 92%